Riboflavin Adsorption On Mesoporous Carbon By Using Aspen Adsorption Simulation - Suhaimi, Muhammad Alif (Universiti Sains Malaysia, 2021)
Riboflavin is one of the B vitamins and essential component of flavin mononucleotide and flavin adenine dinucleotide. Riboflavin is yellow and naturally fluorescent when exposed to ultraviolet light. In this project, adsorption of riboflavin was analysed using Aspen Adsorption software. There are 3 condition that considerperforming this simulation which is initial flow rate (10, 20, and 30 mL/min at constant bed height and initial concentration of RF, 2 cm and 50 ppm respectively), bed height (changing the bed height 2 , 4, and 6 cm at constant initial flowrate and initial concentration of RF, 10 mL/min and 50 ppm respectively), and initial concentration varied the initial concentration at 50, 100, and 200 ppm at constant initial flow rate 10 mL/min and 2 cm bed height). Taking 303.15 K for the fixed temperature for all the simulation. Breakthrough curve of riboflavin adsorption show shorter time taken to reach the breakthrough point by increasing the initial flow rate and initial concentration of riboflavin for both simulation and experimental. Otherwise, increasing the bed height will give negative result on adsorption of riboflavin. The study of riboflavin adsorption also being analysed by using three different model development ( Thomas, Yoon-Nelson, and Adam-Bohart ). The result show Thomas Model and Yoon-Nelson Model exhibit better performance than Adam-Bohart by analysing the R2value.